Legal Responses to Antisemitism: Legal Discourse and Anti-Jewish Hate in Contemporary Canada - Hollinger, Megan (Université d'Ottawa / University of Ottawa, 2020)
Antisemitism is a pervasive social issue in Canada. A common response is to invoke the law. Law is expected to bring justice to perpetrators and solace to impacted individuals and communities. This thesis examines legal responses to antisemitic hate crimes over the last 12 years (the cases span the years 2008-2017). More specifically, it performs a discourse analysis on four provincial hate crime cases, all pertaining to antisemitic crimes. It addresses the following question: how does law frame and characterize Jewish identity and antisemitism and how do these conceptualizations affect its ability to deter and combat anti-Jewish hate in contemporary Canada? This thesis argues that through its procedural and methodological limitations, law is not efficient enough to be a main deterrent and combatant for antisemitism in contemporary Canada. In other words, how law frames and delimits particular phenomena and issues affect its ability to combat antisemitism. This thesis reveals that courts have tended to construct both Jewish identity and antisemitism in limited ways, portraying Jews as solely religious or racial and excluding important instances of new antisemitism from their decisions. Both Jewish identity and antisemitism are fluid, expressed and experienced in a variety of religious and nonreligious ways. Courts frequently overlooked the nuances that make both unique, instead constructing antisemitic crimes in particular ways that decontextualized its responses. In addition, my thesis reveals how courts further decontextualized their decisions through reducing their focus on the broader social harm and impact of hate and antisemitism.
Keywords: Antisemitism; anti-Jewish hate; new antisemitism; law; hate crime; Jewish; Judaism; Israel; Zionism; religion and law; courts; police